Grip force and pressure distribution analysis of three badminton forehand overhead strokes of male and female players: A case study - Pan, K.-M.; Kao, F.; Tsai, C.-L. (Journal of Physical Education and Sport, 2024)
Badminton players rely on their hands to grip and control the racket face during play. This study aimed to explore how players use their fingers to manipulate the racket, an area with limited dynamic analysis in existing research. Specifically, we examined the distribution of grip force and pressure during three forehand strokes - drop, clear, and smash - between male and female university players. The grip distribution analysis focused on 18 regions of the dominant hand. A Phantom high-speed digital camera and palm pressure sensors were synchronized to capture 2-D kinematic data and record finger force and pressure signals from the preparation phase to the point of contact and follow-through. The results showed that male player performed higher smash velocity compared to female player. The greatest finger force and pressure of clear and smash strokes were appeared at distal phalanx of the middle finger in both genders. The finger force distribution at the point of contact for clears and smashes was similar between male and female participants, yet differed for the drop shots. As shuttlecock velocity increased, the upswing duration time decreased, and the maximum resultant finger force and pressure, the peak resultant finger force and pressure at the contact point increased. The results of the study found that the grip distribution during the forehand stroke. Grip strength training should be identified as crucial for enhancing shuttle velocity. This study provides valuable insights into badminton biomechanics and finger force dynamics, aiding badminton players and coaches in improving badminton technique performance.